Optimization of Performance in Cloud Data Streaming: Comprehensive Review - Hussein , Suhad S.; Hussein, Karim Q. (International Journal of Membrane Science and Technology, 2023)
With the proliferation of cloud computing, the landscape of data processing has undergone a transformative shift. Cloud data streaming, a linchpin of real-time data processing, has emerged as a critical enabler for organizations seeking timely insights and informed decision-making. However, optimizing the performance of cloud data streaming systems poses intricate challenges that necessitate exploration. This comprehensive review article navigates the multifaceted terrain of enhancing performance in cloud data streaming. It encompasses foundational concepts, performance evaluation metrics, prevalent challenges, advanced optimization strategies, illustrative case studies, comparative analysis of platforms, anticipatory trends, and directions for further research.